1990
DOI: 10.2105/ajph.80.6.663
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of severe mental disorder among male urban jail detainees: comparison with the Epidemiologic Catchment Area Program.

Abstract: This paper presents the prevalence rates of schizophrenia and major affective disorders by age and race among a random sample ofmalejail detainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
264
0
11

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 543 publications
(286 citation statements)
references
References 34 publications
9
264
0
11
Order By: Relevance
“…Verificou-se Esquizofrenia, psicopatologia e crime violento: uma revisão reVisÃo De LiterAturA 5% (n = 85) de homicidas com diagnóstico de esquizofrenia anterior ao crime e concluiu-se haver uma possível associação entre esquizofrenia e condenação por homicídio (Shaw et al, 2006). Outros estudos utilizando metodologia semelhante, ou seja, estimativa de prevalência de esquizofrenia entre condenados por homicídio, constataram resultados semelhantes (Teplin, 1990;Eronen et al, 1996). Ainda na Inglaterra, Brugha et al (2005) compararam duas amostras de pacientes com psicose selecionadas de prisões e da comunidade geral, utilizando o questionário semi-estruturado SCAN (Schedules for Clinical Assessment in Neuropsychiatry).…”
Section: Transtornos Mentais Entre Presidiáriosunclassified
“…Verificou-se Esquizofrenia, psicopatologia e crime violento: uma revisão reVisÃo De LiterAturA 5% (n = 85) de homicidas com diagnóstico de esquizofrenia anterior ao crime e concluiu-se haver uma possível associação entre esquizofrenia e condenação por homicídio (Shaw et al, 2006). Outros estudos utilizando metodologia semelhante, ou seja, estimativa de prevalência de esquizofrenia entre condenados por homicídio, constataram resultados semelhantes (Teplin, 1990;Eronen et al, 1996). Ainda na Inglaterra, Brugha et al (2005) compararam duas amostras de pacientes com psicose selecionadas de prisões e da comunidade geral, utilizando o questionário semi-estruturado SCAN (Schedules for Clinical Assessment in Neuropsychiatry).…”
Section: Transtornos Mentais Entre Presidiáriosunclassified
“…After reviewing the results of our 115 telephone interviews and our field notes from the 127 interviews during the 18 site visits, we identified six factors that were consistently found among the most effective jail diversion programs: (1) integrated services, (2) mental health and criminal justice, with educational degrees being of lesser importance. When respondents were asked to describe the kind of case manager who works well in the diversion program, 56% considered knowledge and experience in both criminal justice and mental health to be ideal.…”
Section: Key Factorsmentioning
confidence: 99%
“…A Department of Justice (DOJ) survey found, for example, that roughly 16% of prison and jail inmates have some form of mental illness (Ditton, 1999). A rigorous epidemiologic study of jail detainees in Cook County, Illinois found prevalence rates that, while less than half that of the DOJ study, were nonetheless still nearly five times higher than those of the general population, even after adjusting for the detainees' sociodemographic characteristics (Teplin, 1990). By the mid-1990s these trends, coupled with the downsizing of the public mental health system, had so altered the landscape of mental health service delivery in the US that the Los Angeles County jail had become the nation's largest provider of institutionally-based psychiatric services (Torrey, 1995).…”
mentioning
confidence: 99%